Rumah Gadang Transformation: Assessment on Sustainable Building Materials - Canrath, Gabriella Ananta; Widyarko, Widyarko; Salsabila, Nisrina Dewi (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2022)
The existence of Rumah Gadang is currently threatened due to the rarity of local/traditional materials and the cultural shifts within the Minangkabau people. Some of the surviving Rumah Gadang had undergone modernization in its form due to the use of modern materials such as concrete, zinc, etc. New questions arise whether the application of these modern materials can be considered sustainable for the Rumah Gadang. This study aims to compare the level of sustainability on the Rumah Gadang building material cycle before and after the modernization. This study conducted a case study of Rumah Gadang Padang Laweh, using a qualitative research approach with two data collection methods: observation and interviews. The collected data were then analyzed using the 'Green Feature' parameters, consisting of 15 assessment points. The study reveals that the building materials in the pre-modernized Rumah Gadang (25/30) show a higher sustainability value than the modernized ones (18/45).